Southeast Asian diaspora in the united states memories and visions yesterday, today, and tomorrow - Lee, Jonathan H. X. (Cambridge Scholars Publishing, 2015)
"Southeast Asian Diaspora in the United States: Memories and Visions, Yesterday, Today, and Tomorrow provides various exploratory interpretations of Southeast Asian American subjectivities, communities, histories, creativities, and cultural expressions, as they are revealed, informed, or infused with visions, dreams, and or memories of self in relation to others, places, time, and events."--From back cover.